Experimental study of dynamic characteristics of an ultra-large jacket offshore wind turbine under wind and wave loads using aero-hydro-structural elastic similarities - Xiong, Gen; Lu, Dongzhe; Pan, Zuxing; Wang, Wenhua; Li, Xin; Liu, Qingquan (Frontiers in Energy Research, 2023)
The jacket substructure is generalized for offshore wind farms in the southeastern offshore regions of China. The dynamic characteristics and coupling mechanisms of jacket offshore wind turbines (OWTs) have been extensively investigated using numerical simulation tools. However, limited dynamic model tests have been designed and performed for such types of OWTs. Therefore, the coupling mechanisms of jacket OWTs that are determined using numerical methods require further validation based on experimental tests. Accordingly, an integrated scaled jacket OWT physical test model is designed in this study. It consists of a scaled rotor nacelle assembly (RNA) and support structure model. For the scaled RNA model, a redesigned blade model is adopted to ensure the similarity of the aerodynamic thrust loads without modifying the scaled test winds. Auxiliary scaled drivetrain and blade pitch control system models are designed to simulate the operational states of a practical OWT. The scaled model of the OWT support structure is fabricated based on joint hydro-elastic similarity. A sensor arrangement involving a three-component load cell and acceleration sensors is used to record the OWT thrust loads and model motions, respectively. Then, dynamic model tests under typical scaled wind fields are implemented. Furthermore, the coupling mechanisms of the OWT model under various test winds are investigated using the wavelet packet method, and the influences of inflow winds, operational states, and mechanical strategies are introduced.